Slow deep breathing for hypertensives with poor tissue perfusion - Fauziah, Rizki Agustina; Hidayah, Nurul; Margono, Margono; Seaharattanapatum, Bootsakon (Innovation in Health for Society, 2022)
Hypertension is blood pressure that exceeds normal limits where systolic blood pressure> 140 mmHg and diastolic blood pressure > 90 mmHg. To overcome this, it is necessary to make non-pharmacological therapy, namely the application of slow deep breathing exercises. This study aims to apply the application of slow deep breathing exercise to decrease blood pressure in patients with hypertension with ineffective brain tissue perfusion. The method used in this research is a case study with a sampling technique that is purposive sampling. The results of this study indicate that the application of slow deep breathing exercises can reduce blood pressure in patients with hypertension with ineffective brain tissue perfusion. Slow deep breathing exercises can lower blood pressure by activating the autonomic nerves so that vasodilation occurs in blood vessels. Keywords: Hypertension; nursing care; slow deep breathing; community nursing; nursing intervention